Water‐Assisted Synthesis of Blue Chip Excitable 2D Halide Perovskite with Green‐Red Dual Emissions for White LEDs. Issue 11 (4th July 2019) - Cao, Fei; Yu, Dejian; Xu, Xiaobao; Cai, Bo; Gu, Yu; Dong, Yuhang; Shen, Yalong; Zeng, Haibo
Abstract: White light‐emitting diodes have attracted much attention as indoor solid‐state light‐emitting devices and full‐color displays. The high cost of epitaxial semiconductors for three‐primary‐color multichips compels commercial universality. For traditional yellow downconverters, like YAG and silicates, rare earth element (Ce 3+ or Eu 2+ ) incorporation and high‐temperature manufacture processes impede further development in cost saving. In this work, by an innovative water‐assisted synthesis approach, a series of manganese (Mn)‐doped 2D halide perovskites (HPs) with dual emissions are developed. Systematic experiments elucidate that water in the synthesis process can assist the formation of an intermediate state of HPbI3, which further reacts with the alkylamine for HPs. Significantly, HPs with green‐red dual emissions are achieved for the first time, in which the green emission comes from the 2D HP matrix, and the red emission is owing to exciton transfer from the matrix to Mn (II) centers. By controlling the Mn doping level, the exciton transferring efficiency can be tailored to modulate the overall chromaticity of the emitter. As a result, perfect yellow emission is developed for white light with (0.33, 0.33) color coordinate. It is believed that this work paves the way for the real use of HPs in lighting and display technology. Abstract : A water‐assisted synthesis method is proposed to prepare two‐dimensional halide perovskite with green‐red dual emissions for white light‐emitting diodes. The green and red emissions stem from matrix and doping centers, respectively. Their intensity ratio can be tailored to tune the overall chromaticity of the emitter; therefore, achieving ideal white light with (0.33, 0.33) coordinate when covering commercial blue chips.